Pengaruh pengetahuan dan digitalisasi perpajakan terhadap voluntary tax compliance di mediasi kepercayaan pada industri kecil menengah Jawa Timur - Robiatul Muvidah, Alievia; Andriani, Sri (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this research is to provide empirical evidence regarding: (1) the effect of tax knowledge on voluntary tax compliance. (2) the effect of trust in tax authorities mediating tax knowledge and voluntary tax compliance (3) The effect of tax digitalization on voluntary tax compliance (4) the influence of trust mediating tax digitalization on voluntary tax compliance. In this study, data was collected by distributing questionnaires to obtain 264 samples which were then processed using Smart PLS 3.0 software. In this study, the data analysis technique used was SEM-PLS. The results of this study indicate that knowledge of taxation has a positive effect on voluntary tax compliance, knowledge has a positive effect on trust, and trust has a positive effect on mediating knowledge and voluntary tax compliance. This study also shows the positive effect of tax digitization on voluntary tax compliance and the positive effect of Tax Digitalization on trust, and trust also has a positive influence in mediating tax digitalization on voluntary tax compliance.